The Use of Supplementation Among People Practicing Powerlifting and its Connections with their Self - esteem and Body Value - Andrzej Knapik; Weronika Gallert - Kopyto; Krzysztof Jendrysik; Piotr Ziemianek; Mikołaj Horodecki; Andrzej Myśliwiec (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
Supplementation is one of the forms of powerlifting training support. It may have an influence on physical parameters of the contenders and may also have an impact on perception of the body and self - esteem. The aim of the study was to assess relationships between age, BMI, data concerning training, supplementation, self - assurance and body value among the contenders practising powerlifting.51 people who regularly practise powerlifting: 11 women aged 23.5 ±3.6 and 40 men aged 23.9 ±8.5 have been examined using self - esteem (SES) and body - esteem (BES) questionnaires. Data concerning age, BMI, training variables and supplementation have been also gathered.Supplementation is used by 91% of women and 85% of men. Men use more types of supplements than women (p < 0.05). Among women SES does not correlate with any other variables. Among men SES negatively correlates with the number of used supplements, as well as with all of the BES domains.Using supplementation among people who train powerlifting is rather common. Among women, SES in not related in any way with training or supplementation. Among men, lower self - esteem (SES) is significantly counterbalanced with BES.